Enhancing human islet xenotransplant survival and function in diabetic immunocompetent mice through LRH-1/NR5A2 pharmacological activation - Cobo-Vuilleumier, N.; Lorenzo, P. I.; Martin Vazquez, E.; López Noriega, L.; Nano, R.; Piemonti, L.; Martín, F.; Gauthier, B. R. (Frontiers in Immunology, 2024)
The intricate etiology of type 1 diabetes mellitus (T1D), characterized by harmful interactions between the immune system and insulin-producing beta cells, has hindered the development of effective therapies including human islet transplantation, which requires strong immunosuppressants that impair beta cell survival and function. As such alternative immunomodulating therapies are required for successful transplantation. The discovery that pharmacological activation of the nuclear receptor LRH-1/NR5A2 can reverse hyperglycemia in mouse models of T1D by altering, and not suppressing the autoimmune attack, prompted us to investigate whether LRH-1/NR5A2 activation could improve human islet function/survival after xenotransplantation in immunocompetent mice. Human islets were transplanted under the kidney capsule of streptozotocin (STZ)-induced diabetic mice, and treatment with BL001 (LRH-1/NR5A2 agonist) or vehicle was administered one week post-transplant. Our study, encompassing 3 independent experiments with 3 different islet donors, revealed that mice treated for 8 weeks with BL001 exhibited lower blood glucose levels correlating with improved mouse survival rates as compared to vehicle-treated controls. Human C-peptide was detectable in BL001-treated mice at both 4 and 8 weeks indicating functional islet beta cells. Accordingly, in mice treated with BL001 for 8 weeks, the beta cell mass was preserved, while a significant decrease in alpha cells was observed compared to mice treated with BL001 for only 4 weeks. In contrast, vehicle-treated mice exhibited a reduction in insulin-expressing cells at 8 weeks compared to those at 4 weeks. These results suggest that BL001 significantly enhances the survival, engraftment, and functionality of human islets in a STZ-induced diabetic mouse model.